Population structure of Eupemphix nattereri (Amphibia, Anura, Leiuperidae) from Central Brazil - Silva, Daniela de Melo e (2007)
This study reports on 156 specimens of the amphibian Eupemphix nattereri, a widely distributed leiuperid, obtained from 11 municipalities of central Brazil. The extent of genetic variation was quantified by determining the mean number of alleles per locus and the proportion of polymorphic loci. An analysis of molecular variance (AMOVA) was performed on the random amplified polymorphic DNA (RAPD) haplotypes. The genetic distances obtained by calculating pairwise phist among local samples were used to determine population relationships using the unweighted pair-group method (UPGMA) and non-metric multidimensional scaling (NMDS). The cophenetic correlation was calculated to confirm agreement between the genetic matrix and the unweighted pair group method with averages (UPGMA) dendrogram. To determine if genetic distances were correlated to geographical distances we constructed pairwise genetic distance and geographical distance matrices and compared them using the Mantel test. The AMOVA results indicated significant genetic differences (p < 0.001) between E. nattereri populations, representing 69.5% of the within population genetic diversity. The Mantel test showed no significant correlation (r = 0.03; p = 0.45) between the genetic and geographical distance matrices. Our findings indicate that the genetic variation of E. nattereri populations was randomly distributed in geographic space and that gene flow for this species is probably structured at spatial scales smaller than those between our samples